Strategi 4M Plus Mencegah Dan Mengatasi Demam Berdarah Dengue (DBD) Dikelurahan Jayaloka Kec.Tebing Tinggi Kab.Empat Lawang - Pitriani, Eka; Depriayani, Depriayani; Andeska, Okky; Arlita, Arlita; Ampita, Resmi; Habibi, Julius; Rohani, Tuti; Sari, Fikitri Marya (Universitas Dehasen Bengkulu, 2025)
The number of dengue cases in South Sumatra Province is increasing from year to year. Based on data from all health centers in the Empat Lawang Regency area, a total of 152 residents in Empat Lawang Regency were affected by DHF from January to November 2024, there were 194 cases of DHF in Empat Lawang Regency. The number of cases is also increasing, surpassing the 2023 cases of 18 cases. Dengue fever is a serious health threat in Jaya Loka I Village, which is often triggered by low public awareness of the importance of prevention. The Community Service Program aims to increase the knowledge and awareness of the Kelurahan community about dengue prevention using the 4M Plus strategy (Monitoring mosquito breeding sites, Draining, Covering, Recycling, and additional measures such as the use of larvicides). The methods used include socialization and counseling to Kelurahan residents through digital platforms such as Youtube, interactive presentations, practical demonstrations, and post-evaluation. The results showed an increase in residents' understanding of the 4M Plus strategy. The program succeeded in having a positive impact in reducing the risk of DHF through the implementation of healthy and preventive habits.